FARM SUSTAINABILITY – APROACHES TO MESUREMENT - Поповић, Раде; Кнежевић, Марија; Тошин, Милош (Economics of Agriculture, 2011)
In this article were examined approaches, methods and indicators of farm sustainability. Concept of sustainable development is not defnitive and it will develop in future period. As a consequence, used methods for sustainability assessment are based on simplifcation of theory. Applied indicators are just variables in area one of three sustainability dimensions: economic, environmental and social.